2020
DOI: 10.1186/s41181-020-00107-8
|View full text |Cite
|
Sign up to set email alerts
|

68Ga, 44Sc and 177Lu-labeled AAZTA5-PSMA-617: synthesis, radiolabeling, stability and cell binding compared to DOTA-PSMA-617 analogues

Abstract: Background The AAZTA chelator and in particular its bifunctional derivative AAZTA5 was recently investigated to demonstrate unique capabilities to complex diagnostic and therapeutic trivalent radiometals under mild conditions. This study presents a comparison of 68Ga, 44Sc and 177Lu-labeled AAZTA5-PSMA-617 with DOTA-PSMA-617 analogues. We evaluated the radiolabeling characteristics, in vitro stability of the radiolabeled compounds and evaluated their binding affinity and internalization behavior on LNCaP tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…These findings correlate with the results published by Sinnes et al, who investigated the influence of the exchange of DOTA chelator in DOTA-PSMA-617 against AAZTA 5 . Both DOTA-PSMA-617 and AAZTA 5. -PSMA-617 displayed similar in vitro binding affinities and internalization ratios in LNCaP cells [40]. However, the reported binding affinities and internalization ratios of AATA 5 -PSMA-617 and DOTA-PSMA-617 were higher than those of the SA.KuE conjugates.…”
Section: Discussionmentioning
confidence: 85%
“…These findings correlate with the results published by Sinnes et al, who investigated the influence of the exchange of DOTA chelator in DOTA-PSMA-617 against AAZTA 5 . Both DOTA-PSMA-617 and AAZTA 5. -PSMA-617 displayed similar in vitro binding affinities and internalization ratios in LNCaP cells [40]. However, the reported binding affinities and internalization ratios of AATA 5 -PSMA-617 and DOTA-PSMA-617 were higher than those of the SA.KuE conjugates.…”
Section: Discussionmentioning
confidence: 85%
“…Alternatively, extrapolation of 68 Ga-PSMA-617 uptake on positron emission tomography was previously used for dosimetry of 213 Bi-PSMA-617 ( 20 ). However, recent studies have shown that the degree of radiolabeled PSMA-617 uptake differs based on the radionuclide ( 23 , 24 ), which suggests that independent characterization of 225 Ac-PSMA-617 uptake will improve its dosimetry. At present, the only study that examined the tumor uptake of 225 Ac-PSMA-617 and 177 Lu-PSMA-617 is the pre-clinical study by Current et al ( 21 ), where ex vivo activity measurements were used for accurate uptake estimation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Varasteh et al investigated the influence of four different macrocyclic chelators on a bombesin analog targeting properties ( 97 ), while Renard et al evaluated seven different chelators coupled to a neurotensin receptor 1 antagonist ( 98 ). Other examples of such a strategy also include comparison of [ 68 Ga]Ga-THP-TATE with [ 68 Ga]Ga-DOTATATE and [ 68 Ga]Ga-AAZTA 5 -PSMA-617 with [ 68 Ga]Ga-DOTA-PSMA-617 ( 99 , 100 ).…”
Section: Gallium Chemistrymentioning
confidence: 99%